Optimized methodology for the simultaneous extraction of glucosinolates, phenolic compounds and antioxidant capacity from maca (Lepidium meyenii) - Campos D. (2013)
The authors thank Adelayda Pardo for her technical assistance. This work was supported by the Consejo Nacional de Ciencia y Tecnologia (CONCYTEC), Peru.